DESAIN PEMBELAJARAN BAHASA INGGRIS MELALUI GOOGLE CLASSROOM - Mastoni Mastoni; Rahmawati Rahmawati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The rapid development of technology and the internet in recent years has affected the world of education, especially learning methods. You may still remember the feeling of sitting in a classroom with other friends, while a teacher explained the lesson on the board. This method is still applied, but the technological sophistication influences the change in teaching patterns.One such development emerged through Google Classroom which was officially released in August 2014. As the name implies, Google Classroom tries to